2015
DOI: 10.1016/j.ajo.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis Reactivation in Children Treated With Tumor Necrosis Factor Alpha Inhibitors

Abstract: PURPOSE To evaluate reactivation of pediatric uveitis during/following treatment with TNF-alpha inhibition (anti-TNFα). DESIGN Retrospective cohort study. METHODS We assessed the incidence of uveitis reactivation in children ≤18 years who had achieved uveitis quiescence under anti-TNFα. Survival analysis was used to calculate reactivation rates while still on (primary outcome), and following discontinuation of (secondary outcome), anti-TNFα. Potential predictive factors were assessed. RESULTS Among 50 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
0
20
0
6
Order By: Relevance
“…The Voting Panel recommends that children with controlled CAU on stable medication should be monitored at 3‐month intervals, and those tapering or discontinuing therapy should be monitored at intervals shorter than 3 months, either within 1 month after each change in topical glucocorticoids, and within 2 months of a change in systemic therapy (Figure B). Although the quality of evidence was very low, the recommendations for monitoring were strong due to the potential for harmful consequences of irregular or infrequent monitoring of children with CAU, which could lead to substantial loss of vision and ocular complications from undetected exacerbation of inflammation . Patients were generally concerned about the consequences of infrequent monitoring and agreed that there was little disadvantage to having frequent ophthalmic examinations.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…The Voting Panel recommends that children with controlled CAU on stable medication should be monitored at 3‐month intervals, and those tapering or discontinuing therapy should be monitored at intervals shorter than 3 months, either within 1 month after each change in topical glucocorticoids, and within 2 months of a change in systemic therapy (Figure B). Although the quality of evidence was very low, the recommendations for monitoring were strong due to the potential for harmful consequences of irregular or infrequent monitoring of children with CAU, which could lead to substantial loss of vision and ocular complications from undetected exacerbation of inflammation . Patients were generally concerned about the consequences of infrequent monitoring and agreed that there was little disadvantage to having frequent ophthalmic examinations.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…Although the quality of evidence was very Table 1). | 711 low, the recommendations for monitoring were strong due to the potential for harmful consequences of irregular or infrequent monitoring of children with CAU, which could lead to substantial loss of vision and ocular complications from undetected exacerbation of inflammation (20,25). No recommendations were made for patients with uncontrolled chronic anterior uveitis.…”
Section: Recommendationmentioning
confidence: 99%
“…JIA = juvenile idiopathic arthritis; RF = rheumatoid factor; ANA = antinuclear antibody. | 711 low, the recommendations for monitoring were strong due to the potential for harmful consequences of irregular or infrequent monitoring of children with CAU, which could lead to substantial loss of vision and ocular complications from undetected exacerbation of inflammation (20,25). Patients were generally concerned about the consequences of infrequent monitoring and agreed that there was little disadvantage to having frequent ophthalmic examinations.…”
Section: In Children and Adolescents With Jia And Uveitis That Is Welmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of maintenance therapy on biologic agents is not certain although consensus recommendations suggest continuing treatment for 24 months of inactive disease [39]. One retrospective cohort study (n = 50, 44 % with JIA) has reported on uveitis reactivation after stopping infliximab (n = 45) or adalimumab (n = 5) [64]. Of 19 patients who achieved remission and were subsequently withdrawn from anti-TNFs, 63.8 % had reactivation within 12 months and there did not appear to be an association with duration of medication-induced remission.…”
Section: Biologic Drugsmentioning
confidence: 99%